Recent Advances in Pathogenesis and Anticoagulation Treatment of Sepsis-Induced Coagulopathy - Man C; An Y; Wang GX; Mao EQ; Ma L (Journal of Inflammation Research)
Chit Man,* Yuan An,* Guo-Xin Wang,* En-Qiang Mao, Li Ma Department of Emergency, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Ma; En-Qiang Mao, Email malipostgraduate2@163.com; maoeq@yeah.netAbstract: Coagulopathy in sepsis is common and is associated with high mortality. Although immunothrombosis is necessary for infection control, excessive thrombus formation can trigger a systemic thrombo-inflammatory response. Immunothrombosis plays a core role in sepsis-induced coagulopathy, and research has revealed a complex interplay between inflammation and coagulation. Different mechanisms underlying sepsis-related coagulopathy are discussed, including factors contributing to the imbalance of pro- and anticoagulation relevant to endothelial cells. The potential therapeutic implications of anticoagulants on these mechanisms are discussed. This review contributes to our understanding of the pathogenesis of coagulopathy in patients with sepsis. Recent studies suggest that endothelial cells play an important role in immunoregulation and hemostasis. Meanwhile, the non-anticoagulation effects of anticoagulants, especially heparin, which act in the pathogenesis of coagulopathy in septic patients, have been partially revealed. We believe that further insights into the pathogenesis of sepsis-induced coagulopathy will help physicians evaluate patient conditions effectively, leading to advanced early recognition and better decision-making in the treatment of sepsis.Keywords: sepsis, coagulopathy, endotheliopathy, immunothrombosis, thromboinflammation, anticoagulant